Evaluasi Kebergunaan (Usability) dan Rekomendasi Penggunaan Google Classroom untuk Blended Learning di Perguruan Tinggi - Agus Priyadi; Eko Sediyono; Hindriyanto Dwi Purnomo (JSINBIS (Jurnal Sistem Informasi Bisnis), 2021)
The google classroom application is a virtual classroom mixed with real classes in education where the distribution of material and lecture assignments can be done by teachers and students without using paper or paperless. Interaction between teachers and students is done interactively online. The use of the google classroom application as a teaching tool has only been implemented at XYZ college, so usability testing is needed in the use of google classroom. Testing the usability level of Google Classroom is really needed to evaluate and get recommendations about using the Google Classroom application. The method used in this study is the USE (Usefullness, Satisfaction and Ease of Use) Questionnaire and Cognitive Walkthrough (CW) used in the google classroom usability test. USE stands for Usefulness, Satisfaction, and Ease of Use. Ease of use factors can be divided into two, namely Ease of Learning and Ease of Use. The USE test involved all XYZ college students, totaling 213 respondents. Ten respondents within certain criteria were selected by purposive sampling technique to test the usefulness of using the cognitive walkthrough (CW) method. The overall assessment of the usefulness factor with a mean value of 3.95 is included in the "Good" rating range. Overall, the satisfaction factor value of 4.01 is included in the "Good" rating range. Overall, the assessment of the Ease of use indicator with a mean of 4.22 is included in the "Good" rating range. The cognitive walkthrough (CW) method produces several recommendations that can be utilized by XYZ universities in implementing blended learning using google classroom. The usability factor with various features offered by Google Classroom is quite high because it can provide convenience in its use to support lecture activities at XYZ College